Training in congenital interventional cardiology: interviews with experts from around the globe – part one - Goreczny, Sebastian; A. Qureshi, Shakeel; Hijazi, Ziyad; C. Marshall, Audrey; M. Zahn, Evan; Kim, Sung-Hae; Callahan, Ryan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2020)
The foundation of wisdom is rooted in experience, and thus we reflexively call upon our senior leaders, mentors, coaches, and family members for guidance in our personal and professional lives. Witnessing the weathered perspectives of others allows for an internal audit of one’s own strengths and deficiencies, which ultimately inspires personal growth. This experience is heightened when both the mentor and the mentee, for example, share a common goal. The field of congenital interventional cardiology, with its constant evolution and diverse technical approaches, requires a lifetime of learning, as well as safe passage of knowledge to the next generation. While there are published recommendations for what to consider when completing this task, hearing the sentiments of those with experience may be more profitable for future fellows and current interventionalists. In part one of a series, we hope to accomplish this goal by presenting an opportunity to learn from our experienced colleagues on the topic of congenital interventional cardiology training. Specifically, we aim to share expert opinions on how to succeed as a congenital interventional fellow, illustrate the diversity of teaching styles and expectations in various healthcare systems, and for the mid-career interventionalists, provide insight into the character traits of a successful mentor of interventional fellows.